Wilayah Prioritas Penanganan Stunting di Jakarta Timur Tahun 2021 - Tris Eryando; Aldila Riznawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Stunting is still a major health problem globally, including in Indonesia with a prevalence of 24.4% in 2021. Various interventions have been carried out by the Government of Indonesia in an effort to reduce the prevalence of stunting, one of which is by mapping the distribution of stunting at the district/city level. East Jakarta is one of the loci for stunting reduction in DKI Jakarta Province, with a prevalence of 13.4%. To find out the priority areas for stunting in East Jakarta, a spatial analysis was carried out using the data classification method and scoring of the number of children under five with stunting and their risk factors using the Quantum GIS application. The mapping results showed that Pasar Rebo, Jatinegara, Cakung, and Matraman subdistricts were the top priority areas for stunting management in East Jakarta City in 2021. Planning for stunting intervention programs in priority areas also needs to take into account risk factors such as toddler immunization, helminthiasis, access to sources drinking water and proper sanitation.Keywords: stunting; mapping; geographic information system ABSTRAK Stunting masih menjadi masalah kesehatan utama secara global, termasuk di Indonesia dengan prevalensi 24,4% pada tahun 2021. Berbagai intervensi dilakukan oleh Pemerintah Indonesia dalam upaya menurunkan prevalensi stunting, salah satunya adalah dengan pemetaan sebaran stunting di tingkat kabupaten/kota. Jakarta Timur merupakan salah satu lokus penurunan stunting di Provinsi DKI Jakarta, dengan prevalensi 13,4%. Untuk mengetahui wilayah prioritas penanganan stunting di kota Jakarta Timur, dilakukan analisis spasial dengan metode klasifikasi data dan skoring terhadap jumlah balita dengan stunting dan faktor-faktor risikonya menggunakan aplikasi Quantum GIS. Hasil pemetaan menunjukkan bahwa Kecamatan Pasar Rebo, Jatinegara, Cakung, dan Matraman menjadi wilayah prioritas utama penanganan stunting di Kota Jakarta Timur pada tahun 2021. Perencanaan program intervensi stunting di wilayah prioritas perlu memperhatikan pula faktor risikonya seperti imunisasi balita, penyakit kecacingan, akses ke sumber air minum dan sanitasi layak.Kata kunci: stunting; pemetaan; sistem informasi geografis